2009
DOI: 10.1175/2009jpo4058.1
|View full text |Cite
|
Sign up to set email alerts
|

Near-Inertial Oscillations and the Damping of Midlatitude Gyres: A Modeling Study

Abstract: The classic wind-driven double-gyre problem for a homogeneous (unstratified) thin aspect ratio fluid is considered, but allowing for the flow to be depth dependent. Linear free modes for which the vertical wavenumber k z 6 ¼ 0 are inertial oscillations, and they are excited with a large-scale stochastic forcing. This produces a background sea of near-inertial oscillations and their interaction with the vertically averaged flow is the focus of this study. In the absence of 3D forcing, the near-inertial motion v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…On the other hand, several studies have observed NIWs transferring energy to balanced flows. Gertz & Straub (2009), for example, on examining the dynamics of wind forced oceanic gyres, found that in regions of the gyre where the balanced flow was weak, particularly at large scales, the balanced flow extracted energy from waves. In a different configuration, investigating strongly nonlinear interactions between NIWs and fronts, Thomas & Taylor (2014) found that NIWs transferred energy to geostrophic currents, this being catalyzed by parametric subharmonic instability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, several studies have observed NIWs transferring energy to balanced flows. Gertz & Straub (2009), for example, on examining the dynamics of wind forced oceanic gyres, found that in regions of the gyre where the balanced flow was weak, particularly at large scales, the balanced flow extracted energy from waves. In a different configuration, investigating strongly nonlinear interactions between NIWs and fronts, Thomas & Taylor (2014) found that NIWs transferred energy to geostrophic currents, this being catalyzed by parametric subharmonic instability.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent theoretical and numerical investigations are beginning to demand a reconsideration of above pathways. Various energetic interactions between balanced flows and inertia-gravity waves have been uncovered, at O(1) Rossby numbers (Gertz & Straub 2009;Taylor & Straub 2016;Barkan et al 2017;Thomas 2017 and references therein) and asymptotically small Rossby numbers (Wagner & Young 2015;Xie & Vanneste 2015;Rocha et al 2018). Nevertheless, these investigations have focused primarily on high baroclinic mode NIWs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such instabilities are however absent from other high‐resolution simulations of upper ocean geostrophic turbulence [ Klein et al , ], calling for further investigation. Now, while internal waves or inertial oscillations may play a role in the forward energy cascade leading to dissipation, it is those forced by other mechanisms, particularly winds, that are likely involved [ Gertz and Straub , ]. In both cases, the focus has moved away from spontaneously generated gravity waves.…”
Section: Impacts and Parameterizationsmentioning
confidence: 99%
“…Another, more remarkable perhaps, is that they alter the slow, balanced oceanic circulation directly through wave-mean-flow interaction processes. Gertz & Straub (2009) put forward the idea that NIWs provide an energy sink for this circulation. Their numerical simulations suggest that this process may be significant and, along with other mechanisms including bottom and surface friction (e.g.…”
Section: Introductionmentioning
confidence: 99%